AASP flooding as a substitute of ASP flooding for chemical eor in carbonate reservoirs - Kalwar, S.A. (Society of Petroleum Engineers, 2016)
Alkali-Surfactant-Polymer (ASP) flooding is the most effective Chemical Enhanced Oil Recovery (CEOR) method applied in sandstone reservoirs. After the successful results in sandstone formations, its usage has been widened to carbonate reservoirs as well. However, ASP application in carbonate reservoirs is less well understood. The main limitation of ASP flooding in carbonate reservoirs is the presence of carbonate minerals. These minerals react with the added chemicals to form insoluble materials called precipitations. Therefore, an ASP formulation was developed by incorporating acrylic acid as a precipitation inhibitor to overcome the precipitation problems. The performance of the Acrylic Acid (AA) with an ASP formulation was evaluated using sodium metaborate, surfactant and polymer. Feasibility of applying AA with ASP formula was demonstrated by comprehensive fluid-fluid compatibility tests, interfacial tension tests, viscosity measurements and coreflooding experiments. Hardbrine composition of 59,940 ppm was used to prepare the ASP formulations in the presence and absence of AA. All the chemicals including, alkalis, surfactants, and polymers were compatible with the hard brine used in this study. The presence of acrylic acid exhibited excellent properties in preventing precipitations as the all solutions remained clear for 30 days at 80 oC. The weight ratio of optimum acid concentration of acid to alkali was found to be 0.6:1.0. No precipitation was observed when using this acid to alkali ratio. Interfacial tension and viscosity tests screened the best chemical formulations which were validated by coreflooding. The core flooding tests showed significant improvement in the oil recovery with the use of AASP and ASP flooding by accomplishing a total oil recovery of 75.7 and 88.7 OOIP respectively. Although, total recovery efficiency of AASP formulation is relatively lower than with ASP, the new AASP formulation can be prepared with any water source such as formation water or seawater. The precipitation inhibitor makes the conventional ASP system more flexible and advantageous for offshore applications by eliminating the need of softening or desalting the seawater. Furthermore, there is no need to remove the calcium and magnesium ions from the injected water as it can be done by using the appropriate concentration of acid and alkali. This eliminates the cost of water treatment equipment and minimizes the use of surface equipment as well. Â© 2016, Society of Petroleum Engineers.